Jail : Managing the Underclass in American Society. - Irwin, John (University of California Press, 2013)
"The path away from America's prison crisis may lead through the jail. While there may be many positive aspects of jails as sites of confinement, especially when compared with the prisons of mass incarceration, Irwin's analysis pointed to features that could make the new jail-based version of mass incarceration even worse. The local nature and relative obscurity of jails means that the level of legal review and due process obtainable in prisons through the persistent efforts of civil rights lawyers may be even harder to maintain in jails. The historic focus of jails on what Irwin called "rabble management" threatens to undermine the opportunity presented by the present prison crisis to rethink America's overreliance on confinement of all kinds (whether prisons, jails, or immigration detention centers). If so, it is vital that those of us committed to reversing the destructive effects of mass incarceration on American democracy and social equality expand our concern and our research from prisons to the jails that may replace them. The re-publication of John Irwin's The Jail: Managing the Underclass in American Society is a most timely aid to that mission.-From the foreword by Jonathan Simon."--